Comparative job production based life cycle assessment of conventional and additive manufacturing assisted investment casting of aluminium: A case study. (20th March 2021) - Prakash, Chander; Singh, Sunpreet; Kopperi, Harishankar; Ramakrihna, Seeram; Mohan, S. Venkata
Abstract: Conventional investment casting (IC) process, despite being one of the highly precise manufacturing processes, is suffering from key intrinsic problems, including acquisitions of the enormous resources and specialized machine tools, long production runs, and dedicated workforce. However, additive manufacturing (AM) could be a viable solution to assist the IC process in dealing with the aforementioned issues as well as to refurbish its environmental sustainability. The present research work aims to compare the Life Cycle Assessment (LCA) of conventional and AM assisted IC processes for producing aluminium castings. Particularly, the emphases have been made on comparing the production cycle times, cost, specific energy consumption, and carbon footprints. Along with this, the quality characteristics of as-cast aluminium specimens have been compared for conceptual validity. The results of the study indicated that the use of AM technology has not only curbed the acquisition of the resources and eliminated the necessity of specialized machine tools, but also has reduced the production cycle time, processing cost, specific energy consumption, and carbon emissions by about 19%, 93%, 70%, and 71%, respectively. Overall, the AM assisted IC process has been observed as a rapid, cost-effective, environmentally sustainable process for the job production run. Highlights: Describes the potential benefits of AM technology in conventional IC process. Outlines the potential benefits of AM assisted IC process. Delivers a cost-effective and environmentally sustainable process for job runs.